Resumption Of Postpartum Fecundability In Rural Guatemala: A Multistate Approach - Pinto Aguirre, Guido (Población y Salud en Mesoamérica)
The purpose of this paper is to investigate and re-estimate the effects of breastfeeding patterns, women's nutritional and health status, and energy expenditure on the timing of resumption of postpartum fecundability (i.e. resumption of postpartum menses) using all the relevant information in the Instituto de Nutrición de Centroamérica y Panamá longitudinal study and a more adequate estimation procedure (hazard models). The data used in this study come from a Longitudinal Study carried out in Guatemala between 1967 and 1979. In this article we use a multi-state hazard model that recognizes different pathways and states in the process of returning to the postpartum fecundability. The model relies on the existence of five states (fully breastfeeding, partial breastfeeding, weaning, infant mortality and menses). It also includes explicitly maternal nutrition and women's energy expenditure as strategic elements of the model. The study shows that the estimated effects of breastfeeding patterns, maternal nutrition and women's work patterns (energy expenditure) on resumption of fecundability in rural Guatemala are strong and significant. The contribution of this paper is to show that application of hazard models with multiple states provides estimates that are consistent with hypotheses relating lactation patterns, maternal nutritional status and maternal external stressors to processes that accelerate (decelerate) resumption of normal menstrual cycles.